Repeated spontaneous intra-tumoural and subarachnoid haemorrhage in an anticoagulated patient with a previously-irradiated vestibular Schwannoma: Case report. (March 2020) - Moscovici, Samuel; Limb, Rebecca; Azriel, Amit; Briggs, Robert; Hall, Nicholas; Kaye, Andrew H.
Highlights: Subarachnoid hemorrhage (SAH) caused by vestibular schwannomas (VS) is rare. Anticoagulation treatment and previous radiation therapy (RT) appear to be a risk factor. Caution is needed when considering RT for treatment of VS in patients on chronic anticoagulation therapy. Abstract: Subarachnoid hemorrhage caused by vestibular schwannomas (VS) is rare with no clear pathological mechanism supported in the existing literature. However, anticoagulation treatment as well as previous radiation therapy appear to be a crucial risk factor for subarachnoid haemorrhage from a VS. We report an unusual case of both intratumoural and subarachnoid haemorrhage in a patient with a VS on anticoagulation treatment previously treated with stereotactic radiosurgery. We emphasize the need for caution when considering the use of radiation therapy for treatment of VS in patients on chronic anticoagulation therapy.